Efficient n-doping and hole blocking in single-walled carbon nanotube transistors with 1,2,4,5-tetrakis(tetramethylguanidino)ben-zene - Schneider, Severin; Brohmann, Maximilian; Lorenz, Roxana; Hofstetter, Yvonne J.; Rother, Marcel; Sauter, Eric; Zharnikov, Michael; Vaynzof, Yana; Himmel, Hans-Jörg; Zaumseil, Jana (ACS nano, 2018)
Efficient, stable, and solution-based n-doping of semiconducting single-walled carbon nanotubes (SWCNTs) is highly desired for complementary circuits but remains a significant challenge. Here, we present 1,2,4,5-tetrakis(tetramethylguanidino)benzene (ttmgb) as a strong two-electron donor that enables the fabrication of purely n-type SWCNT field-effect transistors (FETs). We apply ttmgb to networks of monochiral, semiconducting (6,5) SWCNTs that show intrinsic ambipolar behavior in bottom-contact/top-gate FETs and obtain unipolar n-type transport with 3-5-fold enhancement of electron mobilities (approximately 10cm2V-1s-1), while completely suppressing hole currents, even at high drain voltages. These n-type FETs show excellent on/off current ratios of up to 108, steep subthreshold swings (80-100 mV/dec), and almost no hysteresis. Their excellent device characteristics stem from the reduction of the work function of the gold electrodes via contact doping, blocking of hole injection by ttmgb2+ on the electrode surface, and removal of residual water from the SWCNT network by ttmgb protonation. The ttmgb-treated SWCNT FETs also display excellent environmental stability under bias stress in ambient conditions. Complementary inverters based on n- and p-doped SWCNT FETs exhibit rail-to-rail operation with high gain and low power dissipation. The simple and stable ttmgb molecule thus serves as an example for the larger class of guanidino-functionalized aromatic compounds as promising electron donors for high-performance thin film electronics.